A comparative evaluation of the effectiveness of virtual reality, 3D visualization and 2D visual interactive simulation: an exploratory meta-analysis. (February 2019) - Akpan, Ikpe Justice; Shanker, Murali
Research on the application of 3D visualization and virtual reality (VR) in discrete-event simulation (DES) has received increased attention in the past two decades. The increasing popularity of the 3D display in DES is mainly due to superior display capabilities and the associated benefits that it offers. However, the 2D display also continues to enjoy active use to date, thus provoking some fierce debates questioning the need for the 3D and VR if the 2D interface suffices. Several studies comparing the effectiveness of the different visualization methods also produce different conclusions. This paper undertakes a meta-analysis of the different positions and synthesizes the findings from 162 studies on the impacts of the 2D display versus 3D/VR on user performance on various DES tasks. The results highlight four key findings. First, the perception that the 2D display is more effective for model development is misleading as 3D/VR offers overall better performance and quality of models. Second, 3D/VR enables more effective performance than 2D display for model verification and validation. Third, 3D/VR decreases the time taken for verification, validation, experimentation, and analysis of results, but can increase model development time. Finally, the latent variables such as the application domains and nature of the problems tackled have no direct or indirect influence on the efficacy of the 3D display/VR versus 2D on DES task performance.